Phylogeography of Sulfate-Reducing Bacteria among Disturbed Sediments, Disclosed by Analysis of the Dissimilatory Sulfite Reductase Genes (dsrAB) - Pérez-Jiménez, J. R. (American Society for Microbiology, 2005)
Sediment samples were collected worldwide from 16 locations on four continents (in New York, California, New Jersey, Virginia, Puerto Rico, Venezuela, Italy, Latvia, and South Korea) to assess the extent of the diversity and the distribution patterns of sulfate-reducing bacteria (SRB) in contaminated sediments. The SRB communities were examined by terminal restriction fragment (TRF) length polymorphism (TRFLP) analysis of the dissimilatory sulfite reductase genes (dsrAB) with NdeII digests. The fingerprints of dsrAB genes contained a total of 369 fluorescent TRFs, of which <20% were present in the GenBank database. The global sulfidogenic communities appeared to be significantly different among the anthropogenically impacted (petroleum-contaminated) sites, but nearly all were less diverse than pristine habitats, such as mangroves. A global SRB indicator species of petroleum pollution was not identified. However, several dsrAB gene sequences corresponding to hydrocarbon-degrading isolates or consortium members were detected in geographically widely separated polluted sites. Finally, a cluster analysis of the TRFLP fingerprints indicated that many SRB microbial communities were most similar on the basis of close geographic proximity (tens of kilometers). Yet, on larger scales (hundreds to thousands of kilometers) SRB communities could cluster with geographically widely separated sites and not necessarily with the site with the closest proximity. These data demonstrate that SRB populations do not adhere to a biogeographic distribution pattern similar to that of larger eukaryotic organisms, with the greatest species diversity radiating from the Indo-Pacific region. Rather, a patchy SRB distribution is encountered, implying an initially uniform SRB community that has differentiated over time.